FRI0051 Application of a multiplex gene polymorphism assay for variants associated with rheumatoid arthritis susceptibility - results of 168 snps tested in the optima study. (23rd January 2014) - Waring, J. F.; Devanarayan, V.; Idler, K.; Hong, F.; Smolen, J. S.; Kavanaugh, A.; Kupper, H.; Schulze-Koops, H.; Skapenko, A.
Abstract : Background: Factors related to increased susceptibility to rheumatoid arthritis (RA) have been described, with numerous genes and alleles having been identified that may be associated with the onset of the disease or disease progression. In-depth knowledge about RA susceptibility genes may thus prove useful for the development of future diagnostic tests or personalized therapeutics. Objectives: Previously reported RA susceptibility gene frequencies from patients enrolled in the OPTIMA trial were compared to a control database to identify genetic risk factors for RA. Methods: OPTIMA was a 78-week, multicenter, randomized, double-period, double-blind study designed to assess adalimumab plus methotrexate therapy. The study enrolled 1, 032 early RA patients, of which 921 signed informed consents for genetic analysis. Frequency rates for 168 identified RA susceptibility alleles from 53 genes were compared to the European cohort of the 1000 Genomes Project as a reference control. 1 Genotypic variants were assayed using the Illumina BeadXpress GoldenGate Assay. Deviations in the OPTIMA minor allele frequencies (MAFs) >0.05 were further investigated. Results: The majority of MAFs from the OPTIMA study did not deviate >0.05 from MAFs reported in the European cohort from the 1000 Genomes Project. Five gene SNPs demonstrated a MAF deviation >0.05 compared to reference controls (Table ). The BTLA gene G allele (MAF 0.15 compared to 0.04 control) displayed the highest odds ratio (OR) for RA risk (3.60 OR, 95% CI 2.49 – 5.20); the minor allele was weakly associated with DAS28 baseline score, but significantly more associated with reduced age of study participants suggesting susceptibility to early onset of disease. The PTPN22 gene minor allele was associated with increased RA risk when homozygous, supporting previous findings. 2 STAT4 minor allele homozygosity was associated with higher baseline DAS28 scores; however, HLA-DRB1 and NOS3 were not associated with elevated DAS28 scores in this study. Conclusions: Genes identified with increased RA risk have known roles in autoimmunity including mediation of lymphocyte signaling, proliferation, and differentiation. For five gene SNPs, MAFs in the OPTIMA study differed from a healthy control population, strengthening their potential role in RA susceptibility. References: Clarke et al; Nat Methods. 2012 Apr 27;9(5):459-62. Begovich et al; Am J Hum Genet. 2004 Aug;75(2):330-7. Acknowledgements: AbbVie was responsible for the study design, research, analysis, data collection, interpretation of data, and writing, reviewing, and approving of the publication. Medical writing support was provided by Douglas E. Dylla, PhD, of AbbVie Inc. Disclosure of Interest: J. Waring Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., V. Devanarayan Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., K. Idler Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., F. Hong Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., J. Smolen Grant/research support from: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, and UCB, Consultant for: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, and UCB, A. Kavanaugh Grant/research support from: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, H. Kupper Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., H. Schulze-Koops Consultant for: AbbVie Inc., A. Skapenko: None Declared